Critical Data Routing (CDR) for Intra Wireless Body Sensor Networks - Javed Iqbal Bangash; Abdul Hanan Abdullah; Mohammad Abdur Razzaque; Abdul Waheed Khan (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2015)
Recently, Wireless Body Sensor Network (WBSN) has been emerged as a promising technology to provide medical and healthcare monitoring. It can significantly reduce the health-care cost by providing continuous health monitoring facility to the elderly people suffering from chronic diseases. The life critical and real time medical application of WBSNs requires the assurance of the demanded Quality of Service (QoS) both in terms delay and reliability. This paper proposes Critical Data Routing (CDR) that categorizes the sensory data packets as critical and non-critical data packets. Along with the heterogeneous natured data, it also addresses the high and dynamic path loss and the temperature rise issues caused by postural movement of the human body and electromagnetic waves absorption respectively. The simulation results show that the proposed CDR scheme achieves its designed objective of forwarding the critical data packets within certain time limits and with highest reliability while reducing the temperature rise of the in-body sensor nodes.